A study of Corporate Sustainability Reporting Practices in the Indian Energy sector - Arora, Himanshu; Anwer, Naqui; Narula, Sapna A (Strategic Planning for Energy and the Environment, 2023)
The study examines the sustainability disclosures of the Indian energy companies and maps these with respect to Sustainable Development Goals (SDGs). As a part of the study, eighteen energy companies’ publicly available sustainability disclosure data from their sustainability reports were analysed with respect to their performance towards their SDGs. The study has mapped sustainability disclosures and analysed the company’s contribution towards the SDGs by assessing the linked Global Reporting Initiative (GRI) indicators with the SDGs. To analyse the contribution towards SDGs, the criteria were applied to the GRI – compliant sustainability reports for the selected eighteen major energy companies. As a part of the methodology, the companies were categorized by the size of the companies (market capitalization), type (Govt. Vs Private) and Industry (as per UNFCCC segmentation under the Energy sector). The study discloses that SDG 10 and SDG 11 are among the SDGs for which most of the companies have not disclosed sustainability performance, whereas SDG 4, SDG 5 and SDG 9 are the SDGs for which the most contribution is evident as compared to other SDGs. The study contributes to the understanding of sustainability disclosure practises of the companies that are in different stages of adoption of sustainability reporting. The findings of the study contribute to making the disclosures of the company is more relevant to SDGs. Particularly, it is one of the first studies on Indian energy companies to assess sustainability disclosure performance in the context of SDGs.